2018
DOI: 10.1080/08952841.2018.1510247
|View full text |Cite
|
Sign up to set email alerts
|

Body image, satisfaction with sexual life, self-esteem, and anxiodepressive symptoms: A comparative study between premenopausal, perimenopausal, and postmenopausal women

Abstract: Menopause is an important life transition in women, and it is associated with significant physical and psychological changes. This study aimed at examining how the menopausal transition influences body image and satisfaction with sexual life. To this aim, body image dissatisfaction, sexual dissatisfaction, and self-esteem were compared in three groups of women with distinct menopausal status (premenopausal n = 142, perimenopausal n = 66, or postmenopausal n = 149), while controlling for depressive and anxiety … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 30 publications
(33 reference statements)
2
19
0
Order By: Relevance
“…In our study, the average value of self-esteem was 31.79 for inactive women and 29.74 in active women. This is consistent with the previous study of Sejourne N et al, who reported that postmenopausal women had self-esteems at the level of 32.58 [ 45 ]. However, our results are contrary to results from Switzerland, where the mean value of self-esteem in postmenopausal women was 38.86 [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…In our study, the average value of self-esteem was 31.79 for inactive women and 29.74 in active women. This is consistent with the previous study of Sejourne N et al, who reported that postmenopausal women had self-esteems at the level of 32.58 [ 45 ]. However, our results are contrary to results from Switzerland, where the mean value of self-esteem in postmenopausal women was 38.86 [ 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…Satisfaction with their sex life, country of origin, weight and social media were found to be decisive for satisfaction among women. This finding supported previous studies that indicated a positive correlation between body image and sexual satisfaction [ 48 , 49 , 50 ].…”
Section: Discussionsupporting
confidence: 92%
“…For many women, physical decline represents a dreaded marker of aging. Perimenopause signals important physiological changes that accompany psychological changes that frequently and negatively influence self‐appraisal, body satisfaction, and self‐esteem (Séjourné, Got, Solans, & Raynal, ). Although it would be ideal if women embraced the arrival of menopause with “postmenopausal zest,” a term attributed to famed anthropologist Margaret Mead, not every woman is ready to embrace this change, even in light of the potentially positive outcomes that await.…”
mentioning
confidence: 99%